KOMPETENSI KEPRIBADIAN GURU BERSERTIFIKAT DI SMK KABUPATEN ACEH BARAT - Wanty Khaira; Irman Siswanto (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2020)
Certification is the process of giving educator certificates to teachers who already have academic qualifications, competencies, physically and mentally healthy, and have the ability to realize national education goals. Educator certificates are formal proof as the recognition given to teachers as professionals. This study examines whether there is an influence of educator certificates on the personality competencies of vocational school teachers in West Aceh Regency. This quantitative research seeks to find out whether or not there is an influence of teacher certificates on the personality competence of teachers in vocational schools in West Aceh Regency. The population in this study were certified teachers at vocational high schools in Aceh Barat District. Samples were done by random technique, each school was taken as 10 people as their representatives. Namely 5 teacher certification and 5 non-certification. The results showed a significant influence between teacher certificates with the personal competence of vocational school teachers in the West Aceh Regency. This can be seen in the hypothesis test that teacher certification has a significant effect on teacher personality competencies in vocational schools in West Aceh Regency.